Major Trends in the Development of Aerial Photography Technology for Agricultural Lands - R. K. Kurbanov; Yu. S. Tsench; N. I. Zakharova (Сельскохозяйственные машины и технологии, 2025)
Aerial photography has become an essential tool in agriculture; allowing farmers and agronomists to monitor the condition of agricultural land in real time. (Research purpose) This study aims to conduct a retrospective analysis of the evolution of aerial photography technology in agriculture; establish a chronological framework for its development; and provide a comprehensive overview of its advancements. (Materials and methods) A systematic literature review was conducted using a historical-analytical approach. The analysis included original works by both domestic and international authors; including monographs; scientific journals; conference proceedings; museum exhibits; photographic materials; and publicly available software source codes. (Results and discussion) Four key stages in the development of aerial photography equipment were identified based on advancements in camera technology and the aerial platforms on which they were mounted. A comparative analysis of aerial photography devices was conducted; tracing the evolution from wet collodion plate cameras to modern digital aerial cameras mounted on unmanned aerial vehicles (UAVs). (Conclusions) The development of aerial photography equipment for agricultural land mapping has progressed in leaps rather than through gradual increments. Currently; UAVs equipped with visible-spectrum and multispectral cameras are the most relevant for agricultural applications. Future advancements in digital aerial photography cameras will focus on improving spatial resolution; hybridization; and intelligent functionalities.